Clinico-psychiatric profiles of children with self-harm poisoning - Modi, Narayan Prasad; Das, Dillip Kumar; Shukla, Suprabha (Indian Journal of Child Health, 2015)
Background: Self-harm among young people is increasing day by day and little is known about the reasons young people give for cessation and their link with gender or employment status. Objectives: The aim was to study the psychiatric aspects of self-harm and to look for underlying contributing factors responsible for self-harm. Materials and Methods: Hospital based prospective study conducted in a tertiary hospital in the eastern India. Children between 5 and 15 years of age admitted with poisoning were recruited. Extensive questionnaire was put to the admitted children and their parents. Psychiatric diagnosis and evaluation were made based on Diagnostic and Statistical Manual of Mental Disorders IV criteria. Results: Of 62 children admitted with poisoning, 20 children had self-harm poisoning. Girls outnumbered boys with ratio of 1.8:1. Though the number is less, boys had more severe poisoning requiring longer hospital stay. More than 85% children with self-harm were more than 11 years of age. Incidence was more in low socioeconomic group, and family stress was the most important contributing factor. Out of two children with recurrent self-harm behavior, one had bipolardisorder and other was having major depression. Conclusions: Self-harm poisoning is one of the significant problems in children and adolescent. In the case of recurrent episode, one should evaluate for any underlying psychiatric illness and treat the underlying illness.